2012
DOI: 10.1177/1742395312450178
|View full text |Cite
|
Sign up to set email alerts
|

Coping with chronic complex regional pain syndrome: advice from patients for patients

Abstract: Objective: To explore what advice people currently living with chronic CRPS would offer to another person coming to terms with a diagnosis of chronic CRPS. Methods:Semi-structured interviews with 21 adults (5 male) living with chronic CRPS who had completed a CRPS rehabilitation programme were conducted.Results: Effectively self-managing CRPS required individuals to play an active role. This could only be achieved if they felt they had sufficient control. Means of attaining control involved attaining a level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Brunner et al () explored patients' actual knowledge of CRPS and found it to be limited, potentially undermining their ability successfully to self‐manage the condition. Another study, with individuals undertaking a specialist CRPS in‐patient programme, identified the importance of patients being able to access high‐quality information to increase their knowledge of their condition, normalize their experience and learn new coping strategies (Rodham et al, ). To the best of the authors' knowledge, no study has explored the information needs of a broader patient group, who may or may not have experienced specialist services.…”
Section: Introductionmentioning
confidence: 99%
“…Brunner et al () explored patients' actual knowledge of CRPS and found it to be limited, potentially undermining their ability successfully to self‐manage the condition. Another study, with individuals undertaking a specialist CRPS in‐patient programme, identified the importance of patients being able to access high‐quality information to increase their knowledge of their condition, normalize their experience and learn new coping strategies (Rodham et al, ). To the best of the authors' knowledge, no study has explored the information needs of a broader patient group, who may or may not have experienced specialist services.…”
Section: Introductionmentioning
confidence: 99%
“…The intention was to create a companion wiki page that would complement an existing CRPS wiki page [23] created by professionals but lacking the patients' voice, experience and perception of CRPS. Such an information resource would be useful for both people living with CRPS and health professionals who are not likely in the course of their 7 career to encounter many people living with CRPS [24]. Therefore the opportunity to understand CRPS from the perspective of the person living with the condition will be invaluable in enhancing the ability of health professionals to support and normalise the experiences of those patients they do encounter.…”
Section: Development Of Information Leaflets To Meet the Support Needmentioning
confidence: 99%
“…[3][4][5][6][7]. It is clear that CRPS can have a negative impact on the physical, emotional, social and financial aspects of patients' lives [8].…”
Section: Development Of Information Leaflets To Meet the Support Needmentioning
confidence: 99%
See 2 more Smart Citations